2010
DOI: 10.1016/j.bbi.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Brain dendritic cells in ischemic stroke: Time course, activation state, and origin

Abstract: The immune response to stroke is comprised of inflammatory and regulatory processes. One cell type involved in both innate and adaptive immunity is the dendritic cell (DC). A DC population residing in the healthy brain (bDC) was identified using a transgenic mouse expressing enhanced yellow fluorescent protein (EYFP) under the promoter for the DC marker, CD11c (CD11c/EYFP Tg). To determine if bDC are involved in the immune response to cerebral ischemia, transient (40min) middle cerebral artery occlusion (MCAO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
110
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 50 publications
(75 reference statements)
5
110
0
Order By: Relevance
“…These cells were highly positive for the expression of the dendritic cells marker CD11c and several T cell activation-related molecules, as MHC II, CD80 and CD86. However, this was not observed early after MCAO occlusion, and thus, the initial activation observed in the CNS is most probably dependent on microglial activation rather than on bDCs (Felger JC 2010).…”
Section: Central Nervous System Resident Cells and Strokementioning
confidence: 93%
See 1 more Smart Citation
“…These cells were highly positive for the expression of the dendritic cells marker CD11c and several T cell activation-related molecules, as MHC II, CD80 and CD86. However, this was not observed early after MCAO occlusion, and thus, the initial activation observed in the CNS is most probably dependent on microglial activation rather than on bDCs (Felger JC 2010).…”
Section: Central Nervous System Resident Cells and Strokementioning
confidence: 93%
“…Concerning bDCs, is established that they are important players in the second-hit of brain and spinal cord infiltrating T CD4 cells. Using the murine model for EAE, it was demonstrated that bDCs not only present CNS-derived antigens to T cells, but they also input both Th1 and Th17 phenotype to naïve T CD4 cells (Felger JC 2010). It is interesting to remember that, as discussed in the introduction, both populations play a very relevant role in MS pathogenesis.…”
Section: Central Nervous System Resident Cells and Ms/eaementioning
confidence: 99%
“…Further study is needed to clarify fully the identity and function of these DC-like brain cells. Following stroke, microglia, infiltrated macrophagesmonocytes, and DCs express MHC class II, and costimulatory molecules, thus they can act as APCs in the ischemic brain parenchyma [2,8,10]. However, antigen processing differs between macrophages and DCs, as the latter regulate lysosomal acidification better than the former in order to preserve peptides for T-cell recognition [48].…”
Section: Innate Versus Adaptive Immunity In Strokementioning
confidence: 99%
“…Acute brain damage generates a genuine inflammatory reaction triggered by necrotic neuronal cells that leak their content to the extracellular space and trigger strong innate immune responses involving resident microglia and infiltrating leukocytes [4,5]. Notably, antigen-presenting cells (APC) accumulate in the brain parenchyma during the days that follow experimental stroke [6][7][8][9][10]. These cells express major histocompatibility complex (MHC) class II and co-stimulatory molecules, as well as markers of conventional dendritic cells (DCs).…”
Section: Introductionmentioning
confidence: 99%
“…Those proinflammatory mediators increase the blood brain barrier (BBB) disorder, which causes infiltration of leukocytes and expression of endothelial adhesion molecules [13]. MC's and DC's also contribute to the adaptive immunity by presenting antigens [12,14,15]. Through the blood-brain barrier, which has been disturbed by those pro-inflammatory mediators and chemokine, come T cells.…”
Section: Introductionmentioning
confidence: 99%